2021
DOI: 10.1212/nxi.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived neural progenitors in progressive MS

Abstract: ObjectiveTo determine the long-term safety and efficacy of repeated intrathecal (IT) administration of autologous mesenchymal stem cell-derived neural progenitors (MSC-NPs) in patients with progressive MS by evaluating subjects 2 years after treatment.MethodsTwenty subjects were enrolled as part of a phase I, open-label single-arm study of 3 IT injections of MSC-NPs spaced 3 months apart. Subjects were evaluated for adverse events and disability outcomes including the Expanded Disability Status Scale (EDSS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…On the other hand, there is an increased MCP-1 level after treatment with methylprednisolone [47,48]. Analysis of the CSF biomarker in patients after three intrathecal injections of MSCs-derived neural progenitors, revealed a decrease in MCP-1 and an increase in interleukin 8 levels, that confirmed the immunoregulatory properties of MSCs [49].…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, there is an increased MCP-1 level after treatment with methylprednisolone [47,48]. Analysis of the CSF biomarker in patients after three intrathecal injections of MSCs-derived neural progenitors, revealed a decrease in MCP-1 and an increase in interleukin 8 levels, that confirmed the immunoregulatory properties of MSCs [49].…”
Section: Discussionmentioning
confidence: 74%
“…The tolerability of the treatment was established by a phase 1 doseescalating IT administration study in people with PMS, which supported feasibility and long-term safety with post-treatment improvement of clinical scores in 4 (out of 6) participants (Harris et al, 2016). A follow-up single-arm phase 1 study, comprising 3 IT treatments of MSC-NPs administered at 3month intervals, found an improved mean EDSS score over 12 months of follow-up sustained by 7 (out of 20) participants at 2 years (Harris et al, 2018(Harris et al, , 2021. Effects were found to be more pronounced in ambulatory (low/medium-disability) SPMS participants, rather than (non-ambulatory), PPMS participants.…”
Section: Clinical Evidence For Mscs In Pmsmentioning
confidence: 69%
“…Effects were found to be more pronounced in ambulatory (low/medium-disability) SPMS participants, rather than (non-ambulatory), PPMS participants. Clinical outcomes also included signs of improved muscle strength (70% of participants) and bladder function (50% of participants) (Harris et al, 2018), while cerebrospinal fluid biomarker changes, including a decrease in CCL2 and increases in IL-8, HGF, and CXCL12, were found to reflect treatmentrelated immunoregulatory and trophic effects (Harris et al, 2021). These outcomes have inspired an ongoing placebocontrolled phase 2 crossover trial (NCT03355365), which is recruiting 50 PMS participants to receive a total of 6 IT treatments at 2-month intervals, with functional outcomes (including clinical scores and bladder function) assessed over 36 months of follow-up.…”
Section: Clinical Evidence For Mscs In Pmsmentioning
confidence: 99%
“…In another long-term phase I clinical study which was conducted by Harris et al [ 67 ], 20 patients with progressive MS were enrolled. The patients from 2014 to 2016 received three times IT injections of autologous MSC-NPs at an average dose of 9.4 × 10 6 cells (target dose was 1.0 × 10 7 cells).…”
Section: Mesenchymal Stem Cellmentioning
confidence: 99%